In search of the origins of the Malay architectural heritage - Mohd Nawawi, Norwina; Abdul Majid, Noor Hanita; Hj Mohd Ariffin, Noor Aziah (2010)
Teaching of architectural history to students of architecture leaves so many gaps to the rationale of its claim with no appropriate answer on the Malay heritage. The similarities found in the architectural styles in the Southeast Asian region have triggered many theories among architectural writers and critics. It is important to understand the development of civilisation in the said region that is profoundly connected to the architectural establishment in both styles and typologies. This paper intends to discuss selected theories and review some examples of architectural forms found in Thailand, Indonesia, Malaysia, Cambodia, Laos PDR and Vietnam. The analyses of case studies suggest the similarities and differences of the architectural forms that will explain the origins of the Malay heritage.